Analisis Miskonsepsi Siswa Kelas X pada Materi Virus Menggunakan Tes Diagnostik Multiple Reasoned Choice di Smas Nurul Hasanah Tembung - Renata Devi Pardede; Tri Harsono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze Grade X students’ misconceptions on virus material using a Multiple Reasoned Choice diagnostic test at SMAS Nurul Hasanah Tembung in the 2025/2026 academic year. The study employed a quantitative descriptive method involving 36 students as the research sample. Data were collected through a Multiple Reasoned Choice diagnostic test, questionnaires on misconception factors, and documentation. Data analysis was conducted by calculating the percentage of students’ conceptual understanding categories, namely understanding concepts, misconceptions, and lack of understanding. The results showed that the average percentage of students who understood the concepts was 84%, while 8% experienced misconceptions and 8% did not understand the concepts. The highest misconceptions were found in indicators related to analyzing lytic and lysogenic cycles, identifying virus structures, and analyzing stages of virus assembly. The major factors causing misconceptions were teaching methods at 84.44%, contextual errors at 81.11%, student factors at 79.31%, textbooks at 72.78%, and teachers at 54.44%. The study concluded that most students had understood virus material well, although misconceptions still occurred in several important concepts. Therefore, more innovative and interactive learning strategies are needed to minimize students’ misconceptions.